2017
DOI: 10.1097/txd.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

A Donor Age-Based and Graft Volume–Based Analysis for Living Donor Liver Transplantation in Elderly Recipients

Abstract: BackgroundGiven the expected increase in the number of elderly recipients, details regarding how clinical factors influence the outcome in living donor liver transplantation (LDLT) for the elderly remain unclear. We examined the survival outcomes according to the results of donor age-based and graft volume–based analyses and assessed the impact of prognostic factors on the survival after LDLT for elderly recipients.MethodsThe 198 adult recipients were classified into 2 groups: an elderly group (n = 70, E group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…(29) Imamura et al reported that LDLT outcomes in elderly recipients with grafts from donors aged ≥50 years with graft weight/standard liver volume of <40% were significantly worse than those with other combinations of age and graft weight/standard liver volume. (30) The poor outcome with the older donor age group in our study may be attributed to the effect of aging on the liver's capacity for regeneration. (22) Hidaka et al have attributed that to the significantly fewer Kupffer cells in liver grafts donated from elderly donors than those procured from young donors.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…(29) Imamura et al reported that LDLT outcomes in elderly recipients with grafts from donors aged ≥50 years with graft weight/standard liver volume of <40% were significantly worse than those with other combinations of age and graft weight/standard liver volume. (30) The poor outcome with the older donor age group in our study may be attributed to the effect of aging on the liver's capacity for regeneration. (22) Hidaka et al have attributed that to the significantly fewer Kupffer cells in liver grafts donated from elderly donors than those procured from young donors.…”
Section: Discussionmentioning
confidence: 62%
“…Moon et al reported that ALDLT using a right lobe with GRWR <0.8% can be performed safely when grafts from young donors (<44 years old) are used and attention is paid to MHV tributary drainage . Imamura et al reported that LDLT outcomes in elderly recipients with grafts from donors aged ≥50 years with graft weight/standard liver volume of <40% were significantly worse than those with other combinations of age and graft weight/standard liver volume …”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of age on donor prognosis, it has been reported that the length of hospitalization of liver donors aged >50 years was longer compared with that of young donors; furthermore, the ability of postoperative protein synthesis is decreased, the duration of cholestasis is prolonged, TB levels increase significantly, and the incidence rate of postoperative complications is higher among older patients. And for recipients receiving an elderly donor liver, there is a significant increase in the risk of postoperative microvascular thrombosis [28,29,30]. In our study all of our donors were less than 40yrs and so no effect of age was found on the rate of regeneration.…”
Section: Discussionmentioning
confidence: 53%
“…In particular, a few reports have found that it is now possible to perform hepatectomies safely even in elderly patients who have various complications [20][21][22]. However, there have only been a few studies of perioperative liver regeneration in elderly patients who undergo hepatectomies [23]. Therefore, we compared regeneration of the remnant liver and other aspects of the perioperative course in elderly and non-elderly patients.…”
Section: Discussionmentioning
confidence: 99%